2022
DOI: 10.3389/fcell.2022.900418
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell-Derived Antimicrobial Peptides as Potential Anti-Neoplastic Agents: New Insight into Anticancer Mechanisms of Stem Cells and Exosomes

Abstract: Mesenchymal stem cells (MSCs), as adult multipotent cells, possess considerable regenerative and anti-neoplastic effects, from inducing apoptosis in the cancer cells to reducing multidrug resistance that bring them up as an appropriate alternative for cancer treatment. These cells can alter the behavior of cancer cells, the condition of the tumor microenvironment, and the activity of immune cells that result in tumor regression. It has been observed that during inflammatory conditions, a well-known feature of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 211 publications
0
8
0
Order By: Relevance
“…Exosomes are a subgroup of EVs with an average size of 30-150 nm. [17][18][19] Exosomes are considered longrange intercellular communication tools that transfer various molecules including proteins, DNA, long non-coding RNAs (lncRNAs), message RNAs (mRNAs) and microRNAs (miRs) to the recipient cells.…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomes are a subgroup of EVs with an average size of 30-150 nm. [17][18][19] Exosomes are considered longrange intercellular communication tools that transfer various molecules including proteins, DNA, long non-coding RNAs (lncRNAs), message RNAs (mRNAs) and microRNAs (miRs) to the recipient cells.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Extracellular vesicles (EVs), main agents in cellular paracrine activity, are micro‐ and nano‐sized vesicles which contain bioactive agents and are released by roughly all cells through fusion of multivesicular bodies with the plasma membrane and subsequent release to the intracellular space. Exosomes are a subgroup of EVs with an average size of 30–150 nm 17–19 . Exosomes are considered long‐range intercellular communication tools that transfer various molecules including proteins, DNA, long non‐coding RNAs (lncRNAs), message RNAs (mRNAs) and microRNAs (miRs) to the recipient cells.…”
Section: Introductionmentioning
confidence: 99%
“…One way to quickly rescue and reboot the biological functions of stressed recipient cells is horizontal transfer of mitochondria or mitochondrial genomes from healthy donor cells, in this case, BM MSCs. MSCs are also believed to protect cancerous cells by regulation of cellular metabolism during chemotherapies ( 97 ). Blocking stromal cells to AML cells mitochondrial transfer in BM niche was found to sensitize AML cells to chemotherapy ( 33 ).…”
Section: Mitochondria Trafficking From Mscs To Aml and Addressing Rel...mentioning
confidence: 99%
“…Exosomes can contain quite a few biologically active components such as lipids proteins and nucleic acids and are able to mediate long-distance communication from cell to cell, exchange genetic information, transmit immune signals and even function as a completely independent metabolic unit [ 4 6 ]. Numerous reports have shown that exosomes are involved in the operation of vital cellular physiological activities, especially involving the immune response [ 7 9 ], apoptosis [ 10 12 ], angiogenesis [ 13 – 16 ] and the inflammatory response [ 17 20 ], and they have become potential substitutes for cell-based therapies for various diseases, early diagnostic markers and targeted drug carriers.…”
Section: Introductionmentioning
confidence: 99%